Nuts and CVD - Ros, Emilio (British journal of nutrition, 2015)
Nuts are nutrient-dense foods with complex matrices rich in unsaturated fatty acids and other bioactive compounds, such as l-arginine, fibre, healthful minerals, vitamin E, phytosterols and polyphenols. By virtue of their unique composition, nuts are likely to beneficially affect cardiovascular health. Epidemiological studies have associated nut consumption with a reduced incidence of CHD in both sexes and of diabetes in women, but not in men. Feeding trials have clearly demonstrated that consumption of all kinds of nuts has a cholesterol-lowering effect, even in the context of healthy diets. There is increasing evidence that nut consumption has a beneficial effect on oxidative stress, inflammation and vascular reactivity. Blood pressure, visceral adiposity and the metabolic syndrome also appear to be positively influenced by nut consumption. Contrary to expectations, epidemiological studies and clinical trials suggest that regular nut consumption is not associated with undue weight gain. Recently, the PREvención con DIeta MEDiterránea randomised clinical trial of long-term nutrition intervention in subjects at high cardiovascular risk provided first-class evidence that regular nut consumption is associated with a 50 % reduction in incident diabetes and, more importantly, a 30 % reduction in CVD. Of note, incident stroke was reduced by nearly 50 % in participants allocated to a Mediterranean diet enriched with a daily serving of mixed nuts (15 g walnuts, 7·5 g almonds and 7·5 g hazelnuts). Thus, it is clear that frequent nut consumption has a beneficial effect on CVD risk that is likely to be mediated by salutary effects on intermediate risk factors.